Study on the Changes in Circadian Rhythm Before and After Treatment and the Influencing Factors in Patients with Depression - Guo P; Fang Y; Feng M; Shen Y; Yang S; Wang S; Qian M (Neuropsychiatric Disease and Treatment, 2022)
Ping Guo1,2 *, Yu Fang1 *, Min Feng,1 Yue Shen,1 Shengliang Yang,1 Shikai Wang,1 Mincai Qian1 1Department of Psychosomatic Medicine, Huzhou Third Municipal Hospital, Huzhou, People’s Republic of China; 2Huzhou Third Municipal Hospital Affiliated with Huzhou University, Huzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shikai Wang; Mincai Qian, Department of Psychosomatic Medicine, Huzhou Third Municipal Hospital, No. 2088 in Tiaoxi East Road, Wuxing District, Huzhou, Zhejiang Province, 313000, People’s Republic of China, Tel +86 13665752769 ; +86 13757289002, Email wang_shikaii@163.com; 1311956613@qq.comObjective: To investigate the circadian rhythms of patients with major depressive disorder (MDD) pre-treatment and post-treatment to analyse possible influencing factors.Methods: In this study, we recruited 154 patients in the acute phase of MDD from 10 psychiatric centers in the province. The patients were divided into a morning chronotype group (16– 41 points), an intermediate chronotype group (42– 58 points) and an evening chronotype group (59– 86 points), according to the total scores obtained from the morningness–eveningness questionnaire (MEQ). They were treated randomly with antidepressants, either selective serotonin reuptake inhibitors or agomelatine, for 12 weeks and were evaluated using the MEQ, the 17-item Hamilton Depression Rating Scale (HAMD-17), the Hamilton anxiety scale, the Snaith–Hamilton pleasure scale (SHAPS), the multidimensional fatigue inventory (MFI-20) and the Pittsburgh sleep quality index at the baseline and then at 2, 4, 8 and 12 weeks. The results were analysed by Logistic regression analysis and repeated-measures analysis of variance.Results: The baseline detection rates for the evening, intermediate and morning types were 14.93%, 56.5% and 28.57%, respectively. HAMD-17 scores were significantly lower at weeks 2, 4, 8, and 12 after treatment in patients with different concurrent phenotypes compared with those before treatment (P< 0.05). There were significant differences in gender, age, body mass index, whether depression was first-episode, type of medication, baseline-MEQ and baseline-SHAPS in the chronotype change group compared with the post-treatment chronotype unchanged group (p< 0.05). Logistic regression analysis showed that medication type (P=0.047), baseline MEQ (P=0.001) and baseline SHAPS (P=0.001) were risk factors for improvement in circadian rhythm after treatment for depression.Conclusion: Circadian rhythm disturbances can be adjusted to a normal pattern with effective antidepressant therapy. The medication type, baseline MEQ and baseline SHAPS scores were the influencing factors for the recovery of circadian rhythm disorders.Keywords: major depressive disorder, morningness–eveningness questionnaire, circadian rhythm, chronotype, antidepressant